Prevalence and Associated Factors of Subclinical Mastitis Among Dairy Cows in Ethiopia: A Systematic Review and Meta-Analysis - Tsegaye Asredie Kolech; Abebe Belete Bitew; Sefinew Alemu Mekonnen (Veterinary Medicine International)
Subclinical mastitis (SCM) is an inflammation of the mammary glands without visible changes on milk or under. In dairy cattle production, it is the common and economically significant form of mastitis. Despite such impacts, little is known about its prevalence and associated factors in the different regions of Ethiopia. Hence, this review aimed to estimate the pooled prevalence of SCM from studies reported on Ethiopian dairy cows and explore factors associated with the prevalence of SCM. Articles reporting SCM in the Ethiopian dairy cows, published between 2012 and 2022, were searched from EMBASE, PubMed, Science Direct, Scopus databases, and Google scholar. Article identification, screening, and inclusion were made following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. Data were extracted independently and reviewed by two reviewers, and the trim-and-fill method was used to assess publication bias between studies. Data were managed using statistical tools in … software (Version …). Thirty-four eligible cross-sectional studies were included in the systematic review and meta-analysis. The pooled prevalence of SCM in Ethiopian dairy cows was found to be 43.19% (95% CI: 38.24%–48.13%). It was found that the prevalence of SCM varied between studies (I2 = 97.12%; p<0.001). Based on subgroup and meta-regression analyses, Addis Ababa had the highest estimated prevalence of SCM at 54.11% (95% CI: 40.18–68.03), followed by Amhara region at 52.07% (95% CI: 34.49–69.66). The review revealed that SCM is prevalent in Ethiopian dairy cows, with different factors associated with its prevalence. To ensure dairy cows’ welfare as well minimize the public health risks from the milk, early detection and proper management of SCM would be crucial.